2021
DOI: 10.3390/ma14227031
|View full text |Cite
|
Sign up to set email alerts
|

Additives Imparting Antimicrobial Properties to Acrylic Bone Cements

Abstract: PMMA bone cements are mainly used to fix implanted prostheses and are introduced as a fluid mixture, which hardens over time. The problem of infected prosthesis could be solved due to the development of some new antibacterial bone cements. In this paper, we show the results obtained to develop four different modified PMMA bone cements by using antimicrobial additives, such as gentamicin, peppermint oil incorporated in hydroxyapatite, and silver nanoparticles incorporated in a ceramic glass matrix (2 and 4%). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Other interesting approaches have been reported as alternatives to antibiotics for inclusion in PMMA cement. Robu et al showed that peppermint oil and silver nanoparticles could be incorporated into bone cement, with good biocompatibility and promising antimicrobial effects [ 31 ]. Another recent paper by Jackson et al reported synergistic and extended antibacterial activity by combining gentamicin and silver nitrate in bone cement, which could be of interest for fighting GN-PJIs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other interesting approaches have been reported as alternatives to antibiotics for inclusion in PMMA cement. Robu et al showed that peppermint oil and silver nanoparticles could be incorporated into bone cement, with good biocompatibility and promising antimicrobial effects [ 31 ]. Another recent paper by Jackson et al reported synergistic and extended antibacterial activity by combining gentamicin and silver nitrate in bone cement, which could be of interest for fighting GN-PJIs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results [ 1 ] have demonstrated that the incorporation of peppermint essential oil incorporated in hydroxyapatite, gentamicin, and silver nanoparticles incorporated in ceramic glass (4%) (HUM, GM, and AM2 samples) generated clear areas of inhibition against Staphylococcus aureus ATCC 25923 and Pseudomonas aeruginosa ATCC 27853.…”
Section: Discussionmentioning
confidence: 99%
“…Bone cement is one of the most important biomaterials in hip and knee arthroplasty, and its quality has a great influence on the prosthesis survival rate [ 1 , 2 ]. According to the Canadian Institute for Health Information (CIHI), 84,770 secondary total knee arthroplasty surgeries were done between 2012 and 2020, and their main causes were due to infections (38.4%), prosthesis instability (22.7%), and aseptic loosening (16.5%).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations